Human Reliability Assessment in Critical Operations of Blast Furnace Steering in an Iron Melting Industry - Reza Kazemi; Hematoola Bahredar; Sajad Mousavi; Amin Norozi (Journal of Health Sciences and Surveillance System, 2017)
AbstractBackground: Human errors play a crucial role in the incidence of industrial accidents. Hence, human reliability assessment (HRA) is essential as the most significant element of the system. The present study was conducted aiming at assessing human reliability in steering a blast furnace in an iron melting industry.Methods: The study comprised all HRA stages, namely data collection (through questionnaire), determination of the scope of the study (using interviews and questionnaires), task analysis (through hierarchical task analysis (HTA), determination and identification of errors (SHERPA ), screening, error quantification (HEART), and analysis and effect assessment of human error reduction.Results: A number of 169 errors were identified among 140 Bottom-Level Tasks obtained from HTA diagrams. Among the 38 error producing factors, 22 were identified as effective factors, among which low workforce spirit (19%), excess team members (15.7%), operator inexperience (12.4%), and the poor quality of data transmission through instructions and through person-to-person interaction (11.75%) accounted for the highest effect on the whole operation.Discussion: Human errors in operations for steering blast furnace occur due to a variety of factors, often rooted in various management levels, instructions for steering operations and repair, operators-panels interaction levels, and some factors affecting performance. As a single approach, the techniques used in this study yielded fruitful results. These techniques enjoy high validity though there were signs of technical immaturity, which led to failure in providing consistent control methods.Conclusion: Despite the technical weaknesses in the HRA techniques, currently the HRA is a useful method to enhance the reliability of crucial operations, such as the steering operation of blast furnace.